The experience software-based desine of virtual medical intrascopy systems for simulation study - Аврунін, О. Г.; Averyanova, L. A.; Golovenko, V. M.; Скляр, О. І. (International Journal "Information Technologies and Knowledge", 2008)
Created virtual intrascopy systems allow carry out imitation experiments. Use of e-leaning means is effective method for training of bio-engineers and physicians. These systems may be additional leaning means at study of any high-end technology apparatus.The perspective of this work is design software for creating virtual operation room with several intrascopy systems and modern surgical tools models for surgical planning. This technology is very actually, for example, for neurosurgery planning. This special software will allow surgeon to simulate operation process and choose small-invasive surgical access.